Survey of laceration injuries experienced by US adolescent and young adult alpine skier racers during the 2018-2019 ski season - Bielmeier, C. M.; Man, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Recently during ski racing competitions, a few high-profile accidents resulted in severe life-threatening laceration injuries. Ski-laceration injuries are caused by metal ski edges cutting through skin/muscles/arteries during falls and range in severity. There is a desire by the racing community to better protect skiers. However, current laceration injury research does not provide detailed information about laceration injuries or focus on adolescent and young adult ski racers. Therefore, the Self-Report Slash Injury Survey (Slash Survey) was conducted to (a) measure the frequency, severity, and body location of laceration injuries during skiing and (b) identify the skiing environment and ski maintenance level during laceration injuries. The Slash Survey was an online survey that asked participants ages 10-24, who are enrolled in US ski race programs, to report whether they experienced a laceration injury and what ski maintenance was used during the 2018-2019 ski season. The Slash Survey results suggest that the laceration injury rate during the 2018-2019 ski season was 6.8% and almost half the lacerations reported were considered slight (i.e. <1 day of absence from the sport). For respondents of the survey, no correlation was found between laceration injuries and (a) slope surface conditions, (b) outside temperature, (c) weather, (d) skiing activity, and (e) ski maintenance (tuning). From the survey, the most common ski tuning method was using a file guide by hand (29%), automated ski tune at a ski shop (20%), stone grind (17%), and cup wheel grinder (17%). Furthermore, open-ended responses suggest that a ski community narrative may be amplifying the awareness of laceration injuries. The aim of this survey was to establish detailed information about ski laceration injuries among adolescent and young adult US ski racers for the development of mitigation strategies.